2012
DOI: 10.1371/journal.pone.0043541
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Follow-Up of Occult HCV Infection in an Italian Population Free of Clinically Detectable Infectious Liver Disease

Abstract: BackgroundOccult hepatitis C virus infection (OCI) is a recently described phenomenon characterized by undetectable levels of HCV-RNA in serum/plasma by current laboratory assays, with identifiable levels in peripheral blood mononuclear cells (PBMCs) and/or liver tissue by molecular tests with enhanced sensitivity. Previous results from our group showed an OCI prevalence of 3.3% in a population unselected for hepatic disease. The present study aimed to evaluate OCI prevalence in a larger cohort of infectious l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 30 publications
3
33
2
Order By: Relevance
“…In a follow-up study of people undergoing phlebotomy therapy [28], 6 subjects with OCI were monitored, with only 2 showing detectable HCV infection in PBMCs at 11 and 13 months of follow-up, demonstrating a persistent infection. In the other 4 subjects, none were found to be HCV RNA positive using their PBMCs, even after mitogen stimulation, which demonstrated certain clearance.…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up study of people undergoing phlebotomy therapy [28], 6 subjects with OCI were monitored, with only 2 showing detectable HCV infection in PBMCs at 11 and 13 months of follow-up, demonstrating a persistent infection. In the other 4 subjects, none were found to be HCV RNA positive using their PBMCs, even after mitogen stimulation, which demonstrated certain clearance.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that OCI has been detected among various patient groups worldwide; for instance, in participants with cryptogenic liver disease [Castillo et al, ; Bokharaei‐Salim et al, ], in at‐risk individuals for HCV infection such as haemodialysis patients [Barril et al, ; Thongsawat et al, ] and haemophilic individuals [Parodi et al, ], in patients with lymphoproliferative disorders [Youssef et al, ; Farahani et al, ], in kidney transplant patients [Baid‐Agrawal et al, ], in candidates for liver transplant with cryptogenic cirrhosis [Keyvani et al, ], in patients with primary and secondary glomerular nephropathies [Castillo et al, ], in patients with active HBV infection [De Marco et al, ], in HIV‐infected individuals [Gatserelia et al, ], and also in general population [De Marco et al, , ]. Of course, there are some reports where researchers have found no signs of this infection for example, in kidney transplant patients [Nicot et al, ], in mixed cryoglobulinemia [Giannini et al, ], in autoimmune disorders [Welker and Zeuzem, ], in patients experiencing an immunodepression condition [Pisaturo et al, ], and in non‐Hodgkin lymphoma [Richiardi et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Seronegative OCI is defined by the presence of HCV-RNA in liver in the absence of anti-HCV or HCV-RNA in serum tested by conventional techniques [Castillo et al, 2004], although these patients may have also HCV-RNA in PBMC and low levels of circulating HCV particles [Castillo et al, 2005;Bartolom e et al, 2007]. Since its first description in patients with cryptogenic hepatitis, seronegative OCI has been found in several clinical conditions and even in apparently healthy individuals [Barril et al, 2008;Roque-Cu ellar et al, 2011;De Marco et al, 2012;Farahani et al, 2013]. Later works showed that viral RNA persists over time in PBMC and in serum, showing that viral replication continues in these patients although at a very low level [Castillo et al, 2011].…”
Section: Discussionmentioning
confidence: 99%